A Practical Guide to the Implementation of Bedside Report in a Critical Care Setting. Issue 3 (July 2021) - Martini, Alaina; Resek, Johnna
Abstract : Blended bedside report increases peer-to-peer accountability among nurses, improves communication between nurses as well as patients, and promotes patient safety. Despite the literature that documents bedside report is best, a practical guide to initiating this process in a hospital setting is lacking. A unit-based council composed of staff nurses and 1 member of nursing management on a neurosurgical intensive care unit designed a unit-wide education initiative involving multiple modalities and peer-to-peer training. This combination led to a successful culture change from traditional report to blended bedside reporting process.